Rancang Bangun Mesin Pencucian Garam Dua Tingkat Skala Kecil - Tika Hafzara Siregar; Setya Permana Sutisna; Edi Sutoyo; Mamat Rahmat; Muhammad Nanang Prayudyanto (PERTETA, 2023)
The economic conditions of salt farmers and the quality of their salt often put them in a weak bargaining position, so the price of salt at the farmer level is low. Small-scale consumption salt processing machines need to be designed to increase the value of salt so the welfare of salt farmers can increase. This study aims to design a salt washing machine to increase the NaCl content and remove other impurities such as CaSO4, MgSO4, MgCl2 and others. The machine is designed with stirrig system by maintaining the baume value in mixture of salt and brine at a value of 25-280Be. The machine is equipped with a baume sensor to control the brine baume value. The variable of washing time is varied to produce the best salt quality. This research has designed a two-level salt washing machine with a 0Be controll system that can wash salt with brine in 50 kg/hours capacity. This machine washes the salt in 2 step process. Salt washing machine driven by a 1.5 HP electric motor to stir the salt with brine so it can dissolve the impurities and retain the NaCl in crystal form. The purity of NaCl in salt increased by 7.5% after being washed for 20 minutes.